Tashkent state transport university (Международный научный журнал «Инженер», 2026)
In this study, the possibilities of purification in natural conditions through streams without covering thecontaminants contained in the drainage waters were studied. During the work, the impact of biological, physicaland chemical processes occurring in open drainage channels on water quality indicators was analyzed. The resultsof the experiment showed that non-covering ditches interact with soil, microflora and plants, serving the naturalpurification of drainage waters. In particular, practical observations have revealed a significant reduction inorganic matter, nitrogen and phosphorus compounds, suspension and other polluting components.The results ofthe study are important in the environmentally and economically efficient formation of drainage systems, in thePrevention of secondary pollution of water used in agriculture. At the same time, it is recommended to optimize,taking into account hydromorphological and environmental conditions, in order to enhance the natural cleaningprocess in non-coating ditches.